2012
DOI: 10.1248/bpb.b12-00361
|View full text |Cite
|
Sign up to set email alerts
|

Screening System of Blocking Agents of the Receptor for Advanced Glycation Endproducts in Cells Using Fluorescence

Abstract: Activation of the receptor for advanced glycation endproducts (RAGE) triggers cellular responses implicated in the pathogenesis of diabetic complications; blockade of RAGE has been shown to inhibit the development of diabetic complications. To develop a screening system to identify novel disruptors of advanced glycation endproducts (AGE)-RAGE binding, we used an AGE-RAGE binding system in RAGE-overexpressing cells; test compounds were screened using this system. To construct human RAGE-overexpressing cells, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Although, IC 50 level of EtOAc- soluble fraction was higher than TMG (0.94±0.01 μg/ml), among the extracts, it has the inhibitory effects on AGEs formation (IC 50 =30.13±1.68 μg/ml; AG, IC 50 = 76.47±4.81 μg/ml). Previous research indicated that genistein has inhibitory effects of AR activity in vitro, AGEs formation, and AGE-RAGE binding in hRAGE-overexpressing cells [9,23]. Next, we examined the inhibitory effects of compounds and extracts on AGEs formation (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, IC 50 level of EtOAc- soluble fraction was higher than TMG (0.94±0.01 μg/ml), among the extracts, it has the inhibitory effects on AGEs formation (IC 50 =30.13±1.68 μg/ml; AG, IC 50 = 76.47±4.81 μg/ml). Previous research indicated that genistein has inhibitory effects of AR activity in vitro, AGEs formation, and AGE-RAGE binding in hRAGE-overexpressing cells [9,23]. Next, we examined the inhibitory effects of compounds and extracts on AGEs formation (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…AGEs formation assay was performed as previously described [23,24]. Bovine serum albumin (BSA, 10 mg/ml, Sigma-Aldrich) in 50mM phosphate buffer (pH 7.4) with containing 0.02% sodium azide to prevent bacterial growth was added to 0.2 M fructose and glucose.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of AGEs occurs as a result of the Maillard reaction, a nonenzymatic modification of proteins, lipids, and nucleic acids by reducing sugars. It has been reported that low‐molecular weight heparin (LMWH; Myint et al, ), a β‐(1,2)‐fructan with branches at O‐6 and terminating with a glucosyl residue (Xiao et al, ), quercitrin (Kim et al, ), and genistein (Jung et al, ) antagonize AGE action on RAGE and have preventive effects on DN. LMWH binds RAGE with an affinity approximately six times higher than AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…A human RAGE (hRAGE)-overexpressing plasmid was constructed as previously described (Jung, Kim, & Kim, 2012). Briefly, full-length human RAGE cDNA (GenBank® accession no.…”
Section: Rage-overexpressing Gmcsmentioning
confidence: 99%